Imperatives of responsibility of research activity of researchers - Petroye, Olha (Filosofiya osvity. Philosophy of Education, 2022)
In this article, the author makes an attempt to analyze the responsibility of research activities of researchers as a systemic phenomenon. The research is based on the combination of the results of the generalization of theoretical provisions with the results of practical developments, reflected in the standards of international and European documents. The author is disclosing the role of responsibility of research activity as a priority area of integration of the domestic research system into the European research area, ERA. The main result and scientific novelty of this article is the generalization of the imperative norms of responsibility of the researcher as the main actor in the system of research activity. An essential aspect of the study of the responsibility of research activities of researchers as a systemic phenomenon is the author’s proposed classification of relevant imperative requirements regulated by international and European standards. Their structure contains such components: general responsibility; ethical and professional responsibility; responsible evaluation of research activities; quality, reliability, and integrity; cross-border cooperation; scientific education and training of researchers; responsibility of young scientists; research processes and results. The author concludes about the multifaceted nature and difficulty of the imperative field of responsibility of research activities of researchers and argues that the behavior of researchers is largely mediated by the nature of the relationship and the level of responsibility of other subjects of the research activity.